The Role of Fungi in the Etiology of Multiple Sclerosis - Benito-León, Julián; Laurence, Martin (Frontiers in Neurology, 2017)
Multiple sclerosis (MS) is a chronic inflammatory disorder of the central nervous system. Infectious triggers of MS are being actively investigated. Substantial evidence supports the involvement of the Epstein–Barr virus (EBV), though other viruses, bacteria, protists and fungi are also being considered. Many links between fungi and diseases involving chronic inflammation have been found recently. Evidence linking MS and fungi is reviewed here. The HLA-DRB1*15 allele group is the most important genetic risk factor of MS, and is a risk factor in several other conditions linked to fungal infections. Many biomarkers of MS are consistent with fungal infections, such as IL-17, chitotriosidase and antibodies against fungi. Dimethyl fumarate, first used as an industrial fungicide, was recently repurposed to reduce MS symptoms. Its mechanisms of action in MS have not been firmly established. The low risk of MS during childhood and its moderate association with herpes simplex virus type 2 (HSV-2) suggest genital exposure to microbes (including fungi) should be investigated as a possible trigger. Molecular and epidemiological evidence support a role for infections such as EBV in MS. Though fungal infections have not been widely studied in MS, many lines of evidence are consistent with a fungal etiology. Future microbiome and serological studies should consider fungi as a possible risk factor for MS, and future clinical studies should consider the effect of fungicides other than dimethyl fumarate on MS symptoms.